2022
DOI: 10.3390/ijerph192215298
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival among Patients Hospitalized for COVID-19 during the First Three Epidemic Waves: An Observational Study in a Northern Italy Hospital

Abstract: The mortality rate of hospitalized COVID-19 patients differed strongly between the first three pandemic waves. Nevertheless, their long-term survival has been poorly assessed. The aim of this study was to compare the clinical characteristics and mortality rates of 825 patients with coronavirus disease 2019 (COVID-19) infection who were hospitalized at the Alessandria hub hospital, in Northern Italy, during the first fifty days of the first three pandemic waves. Each subject was followed in terms of vital statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Other authors report all-cause mortality rates of hospitalized COVID-19 patients during 1 year after discharge ranging from 4.7% to 9.3% [ 22 , 39 , 40 ] although higher mortality rates have been reported in the literature [ 41 , 42 ]. Our results are similar to those reported by Li et al who found a mortality of 11.2% in hospitalized patients with COVID-19 after a mean follow-up of 72.8 days [ 43 ] and with those of Bertolotti et al, who described a post-discharge mortality of 16.2% and an overall mortality of 38.7% [ 44 ] after a 6-month outpatient follow-up period. In addition, the follow-up time was longer in our study, which could lead to higher mortality.…”
Section: Discussionsupporting
confidence: 92%
“…Other authors report all-cause mortality rates of hospitalized COVID-19 patients during 1 year after discharge ranging from 4.7% to 9.3% [ 22 , 39 , 40 ] although higher mortality rates have been reported in the literature [ 41 , 42 ]. Our results are similar to those reported by Li et al who found a mortality of 11.2% in hospitalized patients with COVID-19 after a mean follow-up of 72.8 days [ 43 ] and with those of Bertolotti et al, who described a post-discharge mortality of 16.2% and an overall mortality of 38.7% [ 44 ] after a 6-month outpatient follow-up period. In addition, the follow-up time was longer in our study, which could lead to higher mortality.…”
Section: Discussionsupporting
confidence: 92%